Detection and Comparative Analysis of Methylomic Biomarkers of Rheumatoid Arthritis - Feng, Xin; Hao, Xubing; Shi, Ruoyao; Xia, Zhiqiang; Huang, Lan; Yu, Qiong; Zhou, Fengfeng (Frontiers in Genetics, 2020)
Rheumatoid arthritis (RA) is a common autoimmune disorder influenced by both genetic and environmental factors. To investigate possible contributions of DNA methylation to the etiology of rheumatoid arthritis with minimum confounding genetic heterogeneity, we investigated genome-wide DNA methylation in disease-discordant monozygotic twin pairs. This study hypothesized that methylomic biomarkers might facilitate accurate rheumatoid arthritis detection. A comprehensive series of biomarker detection algorithms were utilized to find the best methylomic biomarkers for detecting rheumatoid arthritis patients using the methylomic data of the peripheral blood samples. The best model achieved 100.00% in accuracy with 81 methylomic biomarkers and a 10-fold cross-validation strategy. Some of the methylomic biomarkers were experimentally confirmed to be associated with the onset or development of rheumatoid arthritis. It is also interesting to observe that many of the detected biomarkers were from chromosome Y, supporting the knowledge that rheumatoid arthritis has a significant gender discrepancy.